Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let Summations

Find an expression for $S_2$ in terms of $S_0$ and $S_1$. Do not need to simplify. If someone could explain this, that would be a real life saver.

share|cite|improve this question
$S_2=x\,\frac{\partial}{\partial x}S_1$ – alex.jordan Dec 5 '13 at 7:15
Vandermonde says these three things are linearly independent for $n\geq2$, so you aren't going to find a linear relation between them. If you allow a derivative operator, you have my comment above. Otherwise you need to allow nonlinear relations as in Andres' answer below. – alex.jordan Dec 5 '13 at 7:19
up vote 0 down vote accepted

I am not sure what kind of expression you are after. Here is a suggestion:

Note that $xS_2=\sum_{k=1}^nk^2x^{k+1}=\sum_{k=2}^{n+1}(k-1)^2x^k$, so $$(1-x)S_2=S_2-xS_2=x-n^2x^{n+1}+\sum_{k=2}^n(k^2-(k-1)^2)x^k, $$ or $$ (1-x)S_2=x-n^2x^{n+1}+\sum_{k=2}^n(2k-1)x^k=x-n^2x^{n+1}+2(S_1-x)-(S_0-1-x), $$ that is,
$$ (1-x)S_2=x-n^2x^{n+1}+2S_1-2x-S_0+1+x $$ or, finally, $$ (1-x)S_2=1-n^2x^{n+1}+2S_1-S_0. $$ Is this the kind of relation you are seeking?

Another typical approach, but more advanced, uses calculus: $S_1'=\sum_{k=1}^n k^2x^{k-1}$, so $$ S_2=xS_1'. $$ A similar relation between $S_1$ and $S_0'$, and the realization that $$S_0=\frac{1-x^{n+1}}{1-x} $$ allows us to find explicit formulas for $S_1,S_2$ in terms of $x$, when $x\ne 1$. (When $x=1$, something different is needed, but it can be proved that the first expression is $n+1$, the second is $\displaystyle \frac {n(n+1)}2$, and the last is $\displaystyle \frac{n(n+1)(2n+1)}6$.) But I suspect this is not the approach you seek.

share|cite|improve this answer
There is an example in the book before that gives $$S_0=\frac{1-x^{n}}{1-x} $$. Then In the exorcise that follows we are supposed to do $S_1=\sum_{k=1}^n kx^{k}$ using the same simplifying process. I get stuck at $$ (1-x)S_1=x-(n+1)x^{n+1} $$ which im not sure how to continue or is correct. Then we are supposed to find for $$S_2 $$ then finally make it in terms as per the orignal question. That may or may not make it clearer – Neal Dec 5 '13 at 7:32
@Neal You have a small typo, it should be $S_0-xS_0=1-x^{n+1}$. – Andrés E. Caicedo Dec 5 '13 at 7:41
Ignore that comment the example in the book for $$S_0 = \sum_{k=0}^{n-1} x^{k}$$ – Neal Dec 5 '13 at 7:42

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.